Prevalence and factors associated with cancellation of elective procedures on surgical wards at Mulago hospital, Uganda - Ogwal, Alfred; Oyania, Felix; Nkonge, Emmanuel; Makumbi, Timothy Kabanda; Galukande, Fred Moses (BMC Surgery, 2019)
Background: Cancellation of elective surgical procedures has been noted to waste resources and with potential to increase morbidity and mortality among 11 patients. This study set out to determine the prevalence and factors associated 12 with cancellation of elective surgical procedures at Mulago Hospital. 13 Methods: A prospective cross-sectional study was conducted from 10th January 2018 to 20th February 2018. We recruited patients of all ages admitted15 on surgical wards and scheduled for elective surgery. Demographic data, 16 diagnoses, specialty of surgery, proposed surgery, theatre and reasons for cancellation were extracted and analyzed using logistic regression. 17 Results: There were 115 procedures canceled out of 400 cases, giving us an 18 prevalence of cancellation of 28.8%. Neurosurgery had the highest cancellation 19 rate at 46.8% (n=29), OR = 2.23, 95% CI (1.22, 4.06). UCI theatre was about 20 two times more likely to have a procedure canceled (OR = 2.12, 95% CI, 21 0.91-4.96). Facility factors contributed 67.8% to overall cancellations. Commonest reason for case cancellations was theatre time run out. There was no 22 procedure canceled due to lack of ICU bed. There was a significant association 23 between specialty and surgical cancellation rate (p < 0.05). 24 Conclusions: The prevalence of cancellation of elective surgical procedures in 25 Mulago Hospital is 28.8% with Neurosurgery having the highest cancellation 26 rate. Two thirds of the factors responsible for procedure cancellations were 27 facility related with more than fifty percent of them being potentially preventable. Quality improvement strategies are necessary in those sub specialties 28 susceptible to procedure cancellations due to facility factors.
Keywords: Cancellation; Elective procedures; Factors; Prevalence